Hubungan FoMo Boneka Labubu terhadap Impulsif Buying Generasi Z di Kota Surabaya - Kartika, Deny; Fardhani, M. Hafiizh; Anggraeni, Rhosita Diah (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study examines the relationship between the Fear of Missing Out (FOMO) phenomenon and impulsive buying behavior in Generation Z in Surabaya City, especially related to the viral Labubu doll on social media. The purpose of the study was to determine whether there is a relationship between Fear of Missing Out (FOMO) and impulsive buying behavior in Generation Z in Surabaya City. A total of 30 Generation Z birth groups from 1997 to 2012 in Surabaya City who had bought Labubu dolls to follow social media trends participated, selected using a non-probability sampling technique, namely purposive sampling. This study uses a quantitative correlational approach through a Google Form questionnaire instrument that is distributed online with Likert scale measurements and product moment correlation tests with SPSS 30 software. The results showed that there was a significant relationship between Fear of Missing Out (FOMO) and impulsive buying behavior. Fear of Missing Out (FOMO) Generation Z tends to encourage impulsive buying behavior.